EFFECTS OF DIFFERENT DOSES OF VITAMIN C ON STRESS AND LYMPHOCYTES PARAMETERS IN LIBRATORY RATS. - Nowfel H.Jassim (Basrah Journal of Veterinary Research)
The studied of effects of vitamin C administration on the leukcocyte counts and testing of exercise of male rats. Rats were divided into 4 groups; the first group contain the control and the other group contain the administration with different doses of ascorbic acid (35mg, 75 mg, and 120 mg/day; respectively. The doses were giving by intra-peritoneal injection. Physiological solution was given to the control group (CON) via the same procedure. Exercise performance was based on swim time to fatigue. Blood samples were taken and evaluated at day 10, 20 and 30 days. The lymphocyte percentage was 55.3 ± 5 % for CON on day 28. For all C groups, the range of the lymphocyte percentage was 54.5 %- 64.1 % (p < 0.001). Swim time was 1.6 ± 0.3 min at day 30. This value was increased to 5.1- 8.4 min for the C groups (p < 0.001).